Tumor glucose metabolism and the T cell glycocalyx: implication for T cell function - Schuurmans, Fabian; Wagemans, Kyra E.; Adema, Gosse J.; Cornelissen, Lenneke A. M. (Frontiers in Immunology, 2024)
The T cell is an immune cell subset highly effective in eliminating cancer cells. Cancer immunotherapy empowers T cells and occupies a solid position in cancer treatment. The response rate, however, remains relatively low (<30%). The efficacy of immunotherapy is highly dependent on T cell infiltration into the tumor microenvironment (TME) and the ability of these infiltrated T cells to sustain their function within the TME. A better understanding of the inhibitory impact of the TME on T cells is crucial to improve cancer immunotherapy. Tumor cells are well described for their switch into aerobic glycolysis (Warburg effect), resulting in high glucose consumption and a metabolically distinct TME. Conversely, glycosylation, a predominant posttranslational modification of proteins, also relies on glucose molecules. Proper glycosylation of T cell receptors influences the immunological synapse between T cells and tumor cells, thereby affecting T cell effector functions including their cytolytic and cytostatic activities. This review delves into the complex interplay between tumor glucose metabolism and the glycocalyx of T cells, shedding light on how the TME can induce alterations in the T cell glycocalyx, which can subsequently influence the T cell's ability to target and eliminate tumor cells.